New names of fossil Cyperaceae of Northern Eurasia - Doweld, Alexander B. (Phytotaxa, 2018)
The fossil-species of Scirpus sensu lato are re-classified in currently recognized distinct genera, Amphiscirpus, Bolboschoenus, Schoenoplectiella and Schoenoplectus. New combinations are validated: Amphiscirpus tertiarius comb. nov., Bolboschoenus kreczetoviczii comb. nov., B. longispermus comb. nov., B. pliocenicus comb. nov., B. wieliczkeviczii comb. nov., Schoenoplectiella dravertii comb. nov., S. juliae comb. nov., S. khachlovii comb. nov., S. kipianiae comb. nov., S. lucens comb. nov., S. meotica comb. nov., S. nikitinii comb. nov., S. palaeobucharica comb. nov., S. palibinii comb. nov., S. ragozinii comb. nov., S. suchovii comb. nov., S. szaferi comb. nov., Schoenoplectus liratus comb. nov., S. lusaticus comb. nov. and S. odessanus comb. nov. A new fossil-species Schoenoplectiella isolepioides sp. nov. is validated instead of invalidly published ‘Scirpus (Schoenoplectus) isolepioides’ Mai & Walther. Fossil Scirpus leptocarpus Negru, being an illegitimate later homonym of extant Scirpus leptocarpus Mueller, is re-named Scirpus novorossicus nom. nov. Carex × notholimosioides nom. nov. (C. limosa × C. paleacea) is proposed to replace the later homonym C. × limosoides Cayouette (extant) non C. limosioides Negru (fossil). Cladium crassum Negru (fossil) is replaced by a new name Cladium transdnestrovicum nom. nov., on account of the earlier homonym, C. crassum (Thwaites) Kükenthal (extant). Fossil-species of the genus Dichostylis, a nomenclaturally superfluous name, and unrecognized genus Acorellus are re-classified and transferred to Cyperus: Cyperus distachyoformis comb. nov., C. germanicus comb. nov., C. maii nom. nov., C. pliocenicus comb. nov., C. protohamulosus comb. nov., C. pygmaeoides comb. nov. and C. waltheri nom. nov. Scirpus khachlovii and S. suchovii are lectotypified for the first time.